Intelligent systems design and applications : 16th International Conference on Intelligent Systems Design and Applications (ISDA 2016) held in Porto, Portugal, December 16-18, 2016 - Madureira, Ana; Abraham, Ajith, 1968-; Gamboa, Dorabela; Novais, Paulo (Advances in intelligent systems and computing, 2017)
This book comprises selected papers from the 16th International Conference on Intelligent Systems Design and Applications (ISDA?16), which was held in Porto, Portugal from December 1 to16, 2016. ISDA 2016 was jointly organized by the Portugual-based Instituto Superior de Engenharia do Porto and the US-based Machine Intelligence Research Labs (MIR Labs) to serve as a forum for the dissemination of state-of-the-art research and development of intelligent systems, intelligent technologies, and applications. The papers included address a wide variety of themes ranging from theories to applications of intelligent systems and computational intelligence area and provide a valuable resource for students and researchers in academia and industry alike.